DATABASE OPTIMIZATION FOR THE ROYAL MENGAJAR APPLICATION SUPPORTING CROWDSOURCED ACADEMIC CONTENT - Iqbal, Muhammad; Junaidi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The development of digital learning systems requires not only effective content delivery but also database consistency and performance, particularly when used at scale by lecturers and students. Weaknesses in database design can lead to data duplication, relational violations, and transaction failures that compromise system reliability. This study designed the Royal Mengajar application using PHP and MySQL, supported by JavaScript, HTML, and Bootstrap 5. The Crowdsourced Academic Content model enables lecturers to contribute learning materials openly, while students evaluate them through a user rating system. The objective of this research is to design and optimize the database architecture of the Royal Mengajar application by implementing multiple control mechanisms—namely views, triggers, transactions, and constraints—to enhance data efficiency, consistency, and integrity in digital learning environments. Database optimization focuses on the use of views to improve query efficiency, triggers to maintain automatic consistency, transactions to ensure atomicity in multi-table operations, and constraints to preserve data integrity. The results show that views reduced the average query execution time to 0.12 seconds, triggers maintained consistency without manual intervention, and constraints achieved 100% referential integrity. The application of these mechanisms significantly improved system speed, reduced data redundancy, and enhanced information reliability, thus reinforcing the sustainability of Royal Mengajar as a community-driven learning platform Keywords: crowdsourced academic content; constraint; database optimization; trigger. Abstrak: Pengembangan sistem pembelajaran digital tidak hanya menuntut penyajian materi, tetapi juga konsistensi serta kinerja basis data ketika sistem digunakan secara masif oleh dosen dan mahasiswa. Kelemahan rancangan database dapat menimbulkan duplikasi data, pelanggaran relasi, dan kegagalan transaksi yang memengaruhi keandalan sistem. Penelitian ini merancang aplikasi Royal Mengajar berbasis PHP dan MySQL dengan dukungan JavaScript, HTML, dan Bootstrap 5. Model Crowdsourced Academic Content memungkinkan dosen berkontribusi secara terbuka, sedangkan mahasiswa melakukan evaluasi melalui user rating system. Tujuan penelitian ini adalah untuk merancang dan mengoptimalkan basis data aplikasi Royal Mengajar melalui penerapan berbagai mekanisme pengendali, seperti view, trigger, transaction, dan constraint, guna meningkatkan efisiensi, konsistensi, dan integritas data dalam sistem pembelajaran digital. Optimalisasi database difokuskan pada penerapan view untuk efisiensi query, trigger untuk menjaga konsistensi otomatis, transaction untuk memastikan atomicity pada operasi multi-tabel, serta constraint guna menjamin integritas data. Hasil pengujian menunjukkan view menurunkan rata-rata waktu eksekusi query menjadi 0,12 detik, trigger menjaga konsistensi tanpa intervensi manual, dan constraint memastikan integritas referensial tercapai 100%. Penerapan mekanisme ini berdampak pada peningkatan kecepatan sistem, berkurangnya redundansi, serta keandalan informasi yang lebih tinggi, sehingga mendukung keberlanjutan Royal Mengajar sebagai platform pembelajaran berbasis kontribusi komunitas. Kata kunci: basis data; optimasi; trigger; constraint; crowdsourced academic content.